Analysis Of Tourism Area Life Cycle in Development of Educative Tourism in Buahan Village, Gianyar, Bali - Ni Putu Ayu Saskarawati; I Kadek Artha Prismawan; I Made Trisna Semara (Lafadz Jaya Publisher, 2023)
The rapid development of tourism has made tourism actors create and innovate in advancing rural tourism. Buahan Village is a village that has the potential to be developed as an educational tourism destination. A village that has natural beauty and extraordinary community expertise has made this village increasingly develop educational tour packages for tourists who want to experience traveling as well as gain experience and knowledge. This study focuses on the educational tourism potential of Buahan Village and TALC analysis. The method used is descriptive qualitative with participatory observation.